LIABILITAS NEGARA ATAS SAMPAH ANTARIKSA OLEH NEGARA PELUNCUR DALAM KEGIATAN KERUANGANGKASAAN BERDASARKAN HUKUM INTERNASIONAL - Iqbal, Firdaus Muhamad; Oktaviani , Jusmalia (Yustitia, 2024)
The era of globalization is characterized by the use of space for various human interests. Many countries launch satellites into space, which causes a new problem: increasing amounts of space waste or space debris. Space debris comes in the form of pieces, fragments, or debris that can have a negative impact on the Earth. Subject to applicable law, the launching country is responsible for any losses incurred from the satellite it launched. However, in practice, it is not easy to determine the state's responsibility for space waste. Therefore, this study aims to explain the complexity between the legal framework and the circumstances in the field. The study uses a juridical-normative approach, with logical analysis as well as sociological and philosophical foundations. The types and sources of data used in this study are secondary data. Data is collected primarily through document study techniques (library research and online research) by inventorying secondary data. The study explains that the country's responsibility for the negative effects of space waste will depend on many factors, making it situational. International efforts are needed to anticipate and arrange mutual agreements to prevent space waste from increasing.